Immunodiagnosis of active tuberculosis. (3rd June 2019) - Halliday, Alice; Masonou, Tereza; Tolosa-Wright, Mica; Mandagere, Vinay; Lalvani, Ajit
ABSTRACT: Introduction : There is an unmet clinical need for improved diagnostic tests for active tuberculosis (TB) to provide high sensitivity for all cases, accelerate time to diagnosis and ensure timely and appropriate treatment. Whilst the measurement of M.tb -specific immune responses is widely used for detecting infection in the absence of TB symptoms (i.e. latent TB infection), there is currently no role for immunodiagnostics in active TB disease. This is primarily due to insufficient sensitivity, and an inability to discriminate between active disease and controlled, latent TB infection. Areas covered : In this review, we focus on recent developments in the use of immune-based tests to provide a point of care test for the rule-in or rule-out of active TB. Expert opinion : Recent studies have demonstrated that second-generation IGRAs have the potential to rule-out active TB, particularly in low burden settings. Newer technological platforms, including systems serology and flow cytometry, offer the means to measure specific M.tb specific immune signatures which have been shown to have a high level of accuracy for active TB. However, it is now crucial that new and promising test undergo validation in clinically relevant cohorts which include the full spectrum of TB patients and differential diagnoses.